Rhoda Fleming $1 (BVolume 3s - Meredith, George, 1828-1909 (Salt Lake City, UT : Project Gutenberg, 2003)
"Rhoda Fleming $1 (BVolume 3" by George Meredith is a novel written during the late 19th century, part of the Victorian literary tradition. The book focuses on a complex interplay of societal expectations, romantic entanglements, and the struggles of its characters, with a particular emphasis on Edward and Algernon as they navigate their relationships and the pressures exerted by women like Mrs. Lovell, leading to dramatic confrontations and moral dilemmas. The opening portion of the narrative sets the stage for a tense atmosphere in which personal honor and societal perceptions clash. It primarily introduces Edward, who is faced with the consequences of his actions regarding a rival, Robert, and the confounding influence of Mrs. Lovell, who seems to manipulate the dynamics among the men. As Algernon expresses his desire to defend his honor by challenging Robert, the narrative delves into the complex emotions of jealousy, masculinity, and the ingrained notions of valor. This section hints at deeper relationships among characters as they prepare for potential dueling and confront their feelings about love, duty, and social standing. (This is an automatically generated summary.)s
Release date is 2003-09-01
This etext was produced by Pat Castevans and David Widger
Keywords: Great Britain -- Social life and customs -- 19th century -- Fiction; Farm life -- Fiction; English fiction -- 19th century; Middle class -- Fiction